Rangeland management for livestock production - Patidar, M.; Kumawat, R. N.; Mathur, B. K. (Indian Farming, 2018)
Rangelands in arid areas are important source of grazing for livestock. The livestock keepers have no control over the climate and overgrazing may lead to deterioration and degradation of the pasturelands. Protection and reseeding along with regular monitoring of changes in range quality and productivity is essential to maintain primary and secondary productivity. Carrying capacity analysis also helps as management guide for sustaining the productivity and improving these lands. Thus developed grazing lands must be utilized as per the carrying capacity.